Facilitating Reflective Writing as a Professional Development Tool among Medical Students - B P Preethi; D B Shubha; Suresh Babu (Journal of Medical Sciences and Health)
Introduction: CBME being implemented requires students to engage reflectively. Here students are required to describe what they have learned from a given situation/scenario, interpret it and its future application. It is observed that reflective writing is not being used for professional development, many times it is copied and pasted from peers. This initiated us to incorporate elements of assessment and constructive feedback to facilitate students to use reflective writing as Professional development tool. Materials and methods: This was an interventional study where students' reflections following ECE and AETCOM sessions were assessed using REFLECT rubric by faculty followed by feedback. Effectiveness of intervention was evaluated using Kirkpatrick model, level 1 by obtaining students' and faculty perceptions, level 2 by grading their reflections. Results: 72 (90%) of students' reflections were in level 1 after first session. With five cyclic reinforcements, 58 (72.5%) progressed to level 3 of true reflection, 4(5%) advanced to level 4 of critical reflection,14 (17.5%) attained level 2 of introspection, only 4(5%) remained in level 1. Both students and faculty perceived that repeated exposures facilitated in-depth understanding and critical analysis of clinical encounters, and internalization of attributes such as professionalism, ethics, empathy, compassion, communication skills. Conclusion: Reflective writing skills are not inherent can be acquired with experiential learning complemented with assessments and feedback. Multiple reinforcements of reflections following ECE and AETCOM sessions facilitated students to internalize clinical reasoning and decision-making skills and sensitized them to professionalism, ethics, empathy, compassion, and basic communication skills thereby contributing to their Professional development.